A study of heavy metals in vegetables product and its health risk assessment - Sa’ari, Amanina; Mohamad Basri, Nur Izzati; Muhammad Azmir, Wan Ainin Sofiya (2020)
This study aimed to determine heavy metal concentration which are cadmium (Cd), copper (Cu), manganese (Mn) and zinc (Zn) in vegetable product which are dried vegetables, canned vegetables and tomato paste. The sample preparation method that is used for this study is wet digestion and being analyzed by using Atomic Absorption Spectroscopy (AAS). After that, SPSS software been used for statistical method. For dried vegetables, the range concentration level for cadmium, copper, manganese and zinc is 0.913 – 3.477 ppm, 0.317 – 5.627 ppm, 1.65 – 9.253 ppm and 2.41 – 17.89 ppm respectively. For canned vegetables, the range concentration level for cadmium, copper, manganese and zinc is 0.63 – 1.03 ppm, 2.4 – 5.53 ppm, 10.32 – 12.17 ppm and 13.08 – 20.05 ppm respectively. For tomato paste, the range concentration level for cadmium, copper, manganese and zinc is 0.417 – 0.725 ppm, 0.9 – 3.092 ppm, 4.767 – 7.967 ppm and 2.1 – 7.425 ppm.